Implementation of the Integrated Curriculum at Aisyiyah Bustanul Athfal 33 Kindergarten, Malang City - Nasikin; Khozin; Samba Sowe (Classroom Experiences, 2025)
To develop the curriculum, a curriculum that can be combined with the religious and general curriculum is needed, namely the integrated curriculum. The purpose of this study was to determine how to implement an integrated curriculum in Kindergarten Aisyah Bustanul Athfal (ABA) 33 in the city of Malang. The research method used is a qualitative methodology, with a qualitative descriptive type. Through observation, interviews, and documentation, data were collected. Data was triangulated after being collected. These results indicate that the development of a curriculum that is by the vision, mission, and goals of the school, as well as outstanding teachers and all staff of TK ABA 33 Malang, reflects piety and instills moral and religious values ​​during the learning process, is the basis for implementing the curriculum. integrated. Then the results of student activities such as prayer, Tahsin, and this are reported as student activity reports. In research at TK ABA 33 Malang, the integral learning strategies used include planning, programming daily, yearly, and semester. A solid dedication is a supporting factor for teachers in carrying out their duties and obligations. The obstacle is that some parents do not understand their children's vision, mission, and goals of the school.